2013
DOI: 10.1002/mnfr.201200646
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic acid concentrations in plasma and urine from men consuming green or black tea and potential chemopreventive properties for colon cancer

Abstract: Scope Tea polyphenols are metabolized by the colonic microflora yielding phenolic metabolites, which may contribute to the health benefits of tea. We determined the serum and urine concentrations of phenolic acids, hippuric acid and polyhydroxyphenyl-γ-valerolactones during green tea (GT) and black tea (BT) administration. The effects of (−)-epigallocatechin gallate (EGCG) and 3,4-dihydroxyphenylacetic acid (3,4-DHPAA) alone and in combination on bioavailability, intracellular metabolism, and antiproliferative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 44 publications
(64 reference statements)
5
72
0
2
Order By: Relevance
“…As the concentration in the colon is much higher than in the circulation with concentration ranging from 46 to 479 µmol/L in human faecal water [59,66], some effects exerted at high doses may still be physiological [67]. Moreover, while phenolic acid intake is usually in the range of 50-900 mg per day, phenolic acids in urines can reach levels close to 1 mmol/day-as urinary phenolic acid largely come from the colonic metabolism of (poly) phenolics, but also other compounds such as benzoic acid and precursors (quinic acid, aromatic amino acid tryptophan, tyrosine, and phenylalanine).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the concentration in the colon is much higher than in the circulation with concentration ranging from 46 to 479 µmol/L in human faecal water [59,66], some effects exerted at high doses may still be physiological [67]. Moreover, while phenolic acid intake is usually in the range of 50-900 mg per day, phenolic acids in urines can reach levels close to 1 mmol/day-as urinary phenolic acid largely come from the colonic metabolism of (poly) phenolics, but also other compounds such as benzoic acid and precursors (quinic acid, aromatic amino acid tryptophan, tyrosine, and phenylalanine).…”
Section: Discussionmentioning
confidence: 99%
“…The bioactivity of specific phenolic acids is less well defined, with examples including 3,4diOHPAA an inhibitor of enzymes involved in detoxification (GSTT2), inflammation (COX-2) and anti-proliferative activity in HCT-116 colon cancer cells [67,70]; 3,4-diOHPPA (3 µM) and 3,4-diOHPAA (3 µM), inhibitors of the pro-inflammatory cytokines such as TNF-a, IL-1b and IL-6 in lipopolysaccharide-stimulated peripheral blood mononuclear cells [70,71]; and gallic acid (882 µM) inhibitor of Clostridium histolyticum in in vitro faecal fermentation [65,72].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the diet and the microbiome is complex. Bacteria can influence cancer risk by metabolizing dietary components and dietary components can influence the composition and activity of the microbiome [10].…”
Section: Colon Cancermentioning
confidence: 99%
“…Most of the polyphenols are flavanols, and EGCG is the most abundant and representative for its putative antineoplastic effect. Green tea plays an important role in reducing cancer risk and in delaying cancer outbreak and recurrence (102) and epidemiological studies have revealed that the incidence of stomach and prostate cancers are low among populations that introduce regularly green tea in their diet. Various experimental studies performed in vivo and in vitro have confirmed the anticancer effects by green tea and/or EGCG (103).…”
Section: Green Tea and (-)-Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 99%